Answer:
x = -2, proven below.
Step-by-step explanation:
3x + 7 + 2(4x+1) = 3(x-1) - 4
3x + 7 + 8x + 2 = 3x - 3 - 4
9 + 11x = 3x - 7
16 + 11x = 3x
16 = - 8x
-2 = x
Answer:Multiply the denominator on the bottom of the fraction by the whole number you are dividing by.
To divide a fraction by a whole number, multiply the bottom of the fraction by this whole number.
The denominator on the bottom of the fraction is 7.
We will multiply 7 by 2.
7 × 2 = 14 and so, 6 / 7 ÷ 2 = 6 / 14 .
Step-by-step explanation:
The answer would be 3 ft.
So bigest to smallest? 1/2, 1/5, 1/6.
If the other way, just flip it around.